(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Infertility is a global health concern affecting millions of couples, with increasing interest in natural remedies that support reproductive health. Durio zibethinus (durian), a tropical fruit used in traditional Southeast Asian medicine, is believed to enhance fertility due to its rich content of bioactive compounds such as tryptophan. Aim: To assess the fertility-enhancing potential of Durio zibethinus by preparing a mother tincture and performing preliminary phytochemical analysis, including qualitative identification of tryptophan. Materials and Methods: Fresh Durio zibethinus fruit was collected from the Nilgiris and processed using the Homoeopathic method of maceration into prepare a mother tincture. Preliminary phytochemical screening was performed to detect major bioactive compounds, further the presence of tryptophan was analyzed using the Hopkins-Cole test, a qualitative biochemical method. Results: Phytochemical analysis revealed the presence of tannins, phenols, saponins, terpenoids, glycosides, steroids, carbohydrates, and proteins, while alkaloids and flavonoids were absent. The Hopkins-Cole test showed a characteristic purple ring at the junction of the sample and acid layer, confirming the presence of tryptophan in the tincture. Tryptophan is known to support serotonin and melatonin synthesis, which influence reproductive hormones and fertility. Conclusion: The detection of tryptophan and other bioactive compounds in Durio zibethinus mother tincture provides a scientific basis for its traditional use as a fertility enhancer. This preliminary study provides a scientific basis for further pharmacological research and clinical validation, and opens the possibility of developing a Novel Homoeopathic remedy for infertility-related conditions.